Effect of the basic surface properties of woven lining fabric on printing precision and electrical performance of screen-printed conductive lines. Issue 11 (June 2020) - Hong, Hong; Hu, Jiyong; Yan, Xiong
Conductive lines are essential for the integration of electronic devices into fabrics, and their direct screen printing on fabrics is a promising, simple and low-cost method for mass-manufactured textile-based conductive lines. However, the intrinsic porous structures and texture characteristic of textiles complicate the diffusion and penetration of conductive ink, and will deteriorate the printing precision and electrical performance of conductive lines. To establish the relationship between the surface characteristics (i.e. porosity, roughness, contact angle) and printing precision as well as electrical performance, the screen-printed conductive lines on six different nylon woven lining fabrics were examined and compared. Moreover, to study the printing precision and the minimum printable line width on woven lining fabric, conductive lines with different widths were screen printed. The results showed that the fabric substrate with the smallest pore size and roughness shows a higher printing precision and lower electrical resistance of screen-printed conductive lines. Relatively, the dynamic contact angle and wetting time of ink on the surface of the fabric have a significant effect on the printing precision. Therefore, the surface structure of the fabric substrate determines to some degree the printing precision of conductive lines, the printable minimum line width and its electrical properties. It is believed that these findings will provide some important support for screen printing flexible electronic devices on woven textiles.